2022
DOI: 10.3390/vaccines10020301
|View full text |Cite
|
Sign up to set email alerts
|

Capturing a Crucial ‘Disorder-to-Order Transition’ at the Heart of the Coronavirus Molecular Pathology—Triggered by Highly Persistent, Interchangeable Salt-Bridges

Abstract: The COVID-19 origin debate has greatly been influenced by genome comparison studies of late, revealing the emergence of the Furin-like cleavage site at the S1/S2 junction of the SARS-CoV-2 Spike (FLCSSpike) containing its 681PRRAR685 motif, absent in other related respiratory viruses. Being the rate-limiting (i.e., the slowest) step, the host Furin cleavage is instrumental in the abrupt increase in transmissibility in COVID-19, compared to earlier onsets of respiratory viral diseases. In such a context, the cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 123 publications
(227 reference statements)
0
9
0
Order By: Relevance
“…When disordered proteins participate in protein-protein interactions, ionic bonds are formed between oppositely charged amino acid side-chains, i.e., salt bridges. Studies (Basu and Biswas, 2018;Roy et al, 2022) have found that the formation of salt bridges contributes to the generation of local rigid structure of IDP, and triggers the disordered to ordered transition of IDP. For example, α -synuclein binds with tubulin to form an inter-chain salt bridge and mediate the transformation of protein conformation (Basu and Biswas, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When disordered proteins participate in protein-protein interactions, ionic bonds are formed between oppositely charged amino acid side-chains, i.e., salt bridges. Studies (Basu and Biswas, 2018;Roy et al, 2022) have found that the formation of salt bridges contributes to the generation of local rigid structure of IDP, and triggers the disordered to ordered transition of IDP. For example, α -synuclein binds with tubulin to form an inter-chain salt bridge and mediate the transformation of protein conformation (Basu and Biswas, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, α -synuclein binds with tubulin to form an inter-chain salt bridge and mediate the transformation of protein conformation (Basu and Biswas, 2018). The arginines of FLCS Spike and the anions of Furin form dynamically Frontiers in Molecular Biosciences frontiersin.org interchangeable and durable salt bridge networks at the Spike-Furin binding interface, which triggers the transition from disorder to order (Roy et al, 2022). Therefore, we believe that the performance of the protein-binding sites predictor can be further improved by adding the feature of salt bridges in disordered proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, protein-peptide interactions were also monitored throughout the simulation time using the Maestro package. For computing the energy terms, following a similar methodology as Roy et al (Roy et al, 2022), the total energy values (kcal/mol) were collected at 10 ps intervals across the 300 ns MD simulation trajectory (a total of 30,000 timestamps) for WT Aβ 1-42 -cyclotide complex and its control trajectory (WT Aβ 1-42 unbound), and mutant Aβ 1-42 (Y10A)-cyclotide complex and its control trajectory (Aβ 1-42 Y10A unbound) using the Simulation Quality Analysis (SQA) module in the Desmond package. The difference in total energy (ΔE) between the cyclotide bound and unbound forms along the time series (i; 10 ps intervals) was calculated using the formulae:…”
Section: Conformational Analysis Of Protein-peptide Complexmentioning
confidence: 99%
“…Furthermore, since the discovery of intrinsically disordered proteins (IDPs), with their characteristic binding promiscuity attributed to their physical flexibility, attempts to understand and design protein disorder transitions ( Bandyopadhyay and Basu, 2020 ; Roy et al, 2022 ) and to address the “globular/ordered–disordered” evolutionary interface ( Nagibina et al, 2020 ) in proteins are among the most intriguing challenges in this field. It is but natural that designs of ordered proteins and IDPs should use different principles and the field is enriching with ideas and findings on both ( Figure 1 ).…”
mentioning
confidence: 99%